Assessing the suitability of flours from five pearl millet (Pennisetum americanum) varieties for bread production - Kanton, R. A. L. (2021)
Flour of five new varieties of improved certified pearl millet (Pennisetum glaucum) were evaluated for their physicochemical, functional properties and performance in bread products. The formulated breads were evaluated by 50 untrained panellists. The flours had colour values of L*(60.0 to 70.4), a* (+0.3 to +1.1) and b*(+4.3 to +10.5), low mean water solubility (3.8 ± 0.1) and swelling properties (4.5 ± 0.1) but high water binding capacity (121.4 ± 2.1). SAR002 (Naaad Kohblug) had the highest protein (11.1%), fibre (1.3%), ash (1.2%) and lower fat (3.6%). SAR001 (Kaanati) had the highest fat (4.3%) and ash (1.5%) but the lowest protein (7.9%). The bread showed no interactive effect (p > 0.05) between variety and replacement level with millet flour. Rather, a significant difference (p < 0.05) was observed for the two factors. Increasing proportions of millet flour in the composite flour resulted in a decrease in attribute and acceptability scores of bread. A mean score of 6.4 (slightly like) was obtained for attribute rating and acceptability of bread to 20% proportion of millet flour. Bread produced from SAR001 was the most accepted.